Impacts of COVID-19 on the finfish aquaculture industry of Bangladesh: A case study. (August 2021) - Hasan, Neaz A.; Heal, Richard D.; Bashar, Abul; Bablee, Alif Layla; Haque, Mohammad Mahfujul
Abstract: The COVID-19 outbreak, and the onset of a new normal, has shocked every entrepreneurial sector in Bangladesh including the burgeoning aquaculture sector. To unpack the COVID impacts on finfish aquaculture, two online based surveys were performed in Mymensingh, Bangladesh using structured questionnaires with 40 farmers to assess the economic feasibility of aquaculture farming, and 120 middlemen of the supply chain to unpack market instability. This was followed up with a further open-ended survey done with 120 consumers to gain a clear view of the marketing insights. Our study has revealed that COVID has resulted in a squeeze on profit for the finfish farmer and has opened up inequalities within the supply chain. Benefit-cost ratio analysis of farming reveals that although carp and other catfish farming remain close to the break-even level, pangasius and tilapia farming was potentially putting the farmers in debt. Whilst the consumers are now paying higher prices for pangasius and carp, and slightly reduced prices for tilapia and other catfish, the finfish farmers were receiving less profits. By contrast, the middlemen have increased their selling prices, presumably to offset increased costs and maintain profitability. To compensate rising operational costs and reduced income, farmers have reduced labor costs through reduction in number of staff and their wages. However, this compensation tool risks frustrating working-class people in rural areas and posing huge socio-economic burdens. Finally, the economic difficulties and a lack of support to process fish imposed by COVID restrictions have switched consumer's attitudes regarding fish as their protein source preference. Graphical Abstract: ga1 Highlights: COVID-19 has jeopardized the finfish aquaculture sector of Bangladesh with rising operational costs. It has reduced the profit margin of finfish farmers and disrupted the product supply chain. COVID-19 has changed attitudes towards fish intake as consumer's become more financially constrained. COVID-19 pandemic reduced number of farm laborers and their wages that caused socio-economic imbalance.